2014
DOI: 10.1080/02646838.2014.883597
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal psychosis – a qualitative study of women’s experiences

Abstract: Objective: This study explored women's experience of puerperal psychosis (PP) and their perceptions of its cause, in order to contribute to an increased understanding of PP and promote consideration of new management perspectives. Background: Out of every 1000 live births, approximately one to two women will develop PP. The numbers are relatively small, yet the consequences can be devastating. Key theoretical explanations for the aetiology of PP are genetic, biochemical and endocrine. A small and relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Early qualitative research in this area indicates that mothers experienced postpartum psychosis as a particular type of mental health difficulty that is distinct to and precipitated by the experience of childbirth (Stewart et al, 2003). During the course of postpartum psychosis, mothers often experience negative thoughts about the baby (Glover, Jomeen, Urquhart, & Martin, 2014), accompanied by feelings of shame and guilt over not being able to care or respond appropriately to her infant (Engqvist, Ferszt, Ahlin, & Nilsson, 2011;Engqvist & Nilsson, 2013). Mothers often reported that family members cannot cope or understand the illness and that this was detrimental to their recovery (Glover et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Early qualitative research in this area indicates that mothers experienced postpartum psychosis as a particular type of mental health difficulty that is distinct to and precipitated by the experience of childbirth (Stewart et al, 2003). During the course of postpartum psychosis, mothers often experience negative thoughts about the baby (Glover, Jomeen, Urquhart, & Martin, 2014), accompanied by feelings of shame and guilt over not being able to care or respond appropriately to her infant (Engqvist, Ferszt, Ahlin, & Nilsson, 2011;Engqvist & Nilsson, 2013). Mothers often reported that family members cannot cope or understand the illness and that this was detrimental to their recovery (Glover et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…, Glover et al . ). It appears that time away from the responsibilities of her home life and a good diet contributed to her recovery.…”
Section: Discussionmentioning
confidence: 97%
“…, Posmontier , Oates & Cantwell , Glover et al . ). It is treated with antipsychotic and mood stabilizers; however, admission is often required to prevent harm to the woman or to any other person, including the child (Doucet et al .…”
Section: Introductionmentioning
confidence: 97%
“…The widened perspective of research findings, provided by the significant heterogeneity in age and time since first postpartum psychosis episode between participants, offers novel insight previously unexplored by other recent qualitative research in this population, which rarely seeks the perspective of women 20 years or further into their recovery from postpartum psychosis. 9 13 However, important and distinct experiences may be elicited by interviewing a more narrowly focused age range or those with more recent experience of postpartum psychosis.…”
Section: Discussionmentioning
confidence: 99%